P-selectin Expression Tracks Cerebral Atrophy in Mexican-Americans - Kochunov, Peter; Glahn, David; Hong, Elliott; Lancaster, Jack L.; Curran, Joanne; Johnson, Matthew; Winkler, Anderson; Holcomb, Henry; Kent, Jack; Mitchell, Braxton; Kochunov, Valeria; Olvera, Rene; et al. (Frontiers in Genetics, 2012)
Background and Purpose. We hypothesized that the P-selectin (SELP) gene, localized to a region on chromosome 1q24, pleiotropically contributes to increased blood pressure (BP) and cerebral atrophy. We tested this hypothesis by performing genetic correlation analyses for thirteen mRNA gene-expression measures from P-selectin and eleven other genes located in 1q24 region and three magnetic resonance imaging (MRI) derived indices of cerebral integrity. Methods. The subject pool consisted of 369 (219F; aged 28-85, average=47.1±12.7 years) normally-aging, community-dwelling members of large extended Mexican-American families. Genetic correlation analysis decomposed phenotypic correlation coefficients into genetic and environmental components among thirteen leukocyte-based mRNA gene expressions and three whole-brain and regional measurements of cerebral integrity: cortical gray matter (GM) thickness, fractional anisotropy (FA) of cerebral white matter (WM) and the volume of hyperintensive WM (HWM) lesions Results. From the thirteen gene expressions, significant phenotypic correlations were only found for the P-and L-selectin expression levels. Increases in P-selectin expression levels tracked with decline in cerebral integrity while the opposite trend was observed for L-selectin expression. The correlations for the P-selectin expression were driven by shared genetic factors, while the correlations with L-selectin expression were due to shared environmental effects. Conclusion. This study demonstrated that P-selectin expression shared a significant variance with measurements of cerebral integrity and posits elevated P-selectin expression levels as a potential risk factor of hypertension-related cerebral atrophy.